The Measure of the General Price Level - Snyder, Carl (The Review of Economics and Statistics, 1928)
N the estimation of the General Price Level, or of all exchanges of goods, services and property, there are two modes of approach. The first is through the Equation of Exchange, or division of the total of payments by a measure of Trade. The second is an of the prices themselves, a weighted combination of all different types of series available. If we had astronomical knowledge of all business transactions in the country, in money, and at the same time a physical or volumetric index of everything exchanged, then we could calculate this General Price Level verv closely. Or if we had the final, or consumption of all goods and services of every sort, and the relative amount of each, we could achieve the same result. And this average price would be the reciprocal of the value of money or of the medium of exchange, that is, the true purchasing power of the dollar. So wide is the sampling of all these things now available, it is the writer's view that we have materials for the approximation of such a puice level, at least as reliable as any of our familiar indexes of commodity prices, cost of living, wages, rents, etc. But this is in part to suggest that these familiar indexes of daily use are scarcely the trustworthy and accurate instruments that they have come, in many minds, to be regarded; that in reality they are simply more or less useful approximations.